Effect of Sintering Mechanism on the Properties of ZrO2 Reinforced Fe Metal Matrix Nanocomposite. (29th October 2015) - Jha, Pushkar; Gupta, Pallav; Kumar, Devendra; Parkash, Om
Abstract : The present paper reports phase, microstructure, and compressive strength of ZrO2 reinforced Fe Metal Matrix Nanocomposites (MMNCs) synthesized by powder metallurgy (P/M) technique. High purity grade iron metal powder was mixed with varying percentage of zirconium dioxide (5–30 wt%), compacted, and sintered in argon atmosphere in the temperature range of 900–1100°C for 1 to 3 hours. X-ray diffraction (XRD) analysis of specimens was done in order to study the phases present and scanning electron microscopy was carried out to determine the morphology and grain size of the various constituents. XRD result shows the presence of Fe, ZrO2, and Zr6 Fe3 O phase. Zr6 Fe3 O phase forms due to reactive sintering and is not reported earlier by researchers throughout the globe. SEM results showed the presence of dense microstructure with the presence of Fe, ZrO2, and some nanosize Zr6 Fe3 O phases.